2013
DOI: 10.1371/journal.pone.0076786
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Attenuates the Exacerbation of the Allergic Eosinophilic Inflammation in High Fat-Diet-Induced Obesity in Mice

Abstract: A positive relationship between obesity and asthma has been well documented. The AMP-activated protein kinase (AMPK) activator metformin reverses obesity-associated insulin resistance (IR) and inhibits different types of inflammatory responses. This study aimed to evaluate the effects of metformin on the exacerbation of allergic eosinophilic inflammation in obese mice. Male C57BL6/J mice were fed for 10 weeks with high-fat diet (HFD) to induce obesity. The cell infiltration and inflammatory markers in bronchoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
74
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(87 citation statements)
references
References 57 publications
1
74
1
Order By: Relevance
“…However, in a chronic asthma model utilizing a different trigger (ovalbumin and fungal-associated allergenic protease), metformin reduced several asthma-related processes including eosinophilic and neutrophilic lung inflammation, peribronchial inflammatory cell infiltration, IgE responses, airway smooth muscle thickness, remodeling-related growth factor expression and airway oxidative stress [110]. In a separate study, metformin also eliminated the normal elevations seen in eotaxin, TNF-alpha, NOx and iNOS expression following murine ovalbumin sensitization and challenge[111]. Shore and colleagues in a study of human airway smooth muscle showed that thiazolidinediones (and possibly metformin) inhibit the production and release of several asthmagenic inflammatory mediators from airway smooth muscle possibly through mechanisms unrelated to AMPK activation [112].…”
Section: Exercise Dietary Components and Weight-loss Drugs: Implicatmentioning
confidence: 99%
“…However, in a chronic asthma model utilizing a different trigger (ovalbumin and fungal-associated allergenic protease), metformin reduced several asthma-related processes including eosinophilic and neutrophilic lung inflammation, peribronchial inflammatory cell infiltration, IgE responses, airway smooth muscle thickness, remodeling-related growth factor expression and airway oxidative stress [110]. In a separate study, metformin also eliminated the normal elevations seen in eotaxin, TNF-alpha, NOx and iNOS expression following murine ovalbumin sensitization and challenge[111]. Shore and colleagues in a study of human airway smooth muscle showed that thiazolidinediones (and possibly metformin) inhibit the production and release of several asthmagenic inflammatory mediators from airway smooth muscle possibly through mechanisms unrelated to AMPK activation [112].…”
Section: Exercise Dietary Components and Weight-loss Drugs: Implicatmentioning
confidence: 99%
“…Notwithstanding, a possible potentiating effect of M1-released chemokines towards T H 2 inflammation in the lungs from obese mice must be considered. It was reported in a recent paper that long-term treatment with metformin in high-fat fed ovalbumin-challenged mice was able to reduce pulmonary eosinophilia by decreasing nitric oxide metabolite (NOx) production as a consequence of inhibition of lung NFkB p65-binding to the iNOS promoter region, which fails to be activated by TNF-α [98]. These data shed light on the possibility of a cross-talk between M1 macrophage-released TNF-α and T H 2-dependent inflammation, which may take place in obesity conditions.…”
mentioning
confidence: 99%
“…This study supplements the possible mechanistic role of metformin in activating 5-adenosine monophosphate-activated protein kinase (AMPK), which is shown to attenuate allergic eosinophilic airway inflammation, 2 to inhibit TNF-α-induced inflammatory signalling 3 and to decrease oxidative stress, 4 thus providing evidence for possible beneficial role of metformin in asthma patients.…”
mentioning
confidence: 66%